1988
DOI: 10.1042/bj2560403
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of cardiac mitochondrial pyruvate dehydrogenase activity on intramitochondrial free Ca2+ concentration

Abstract: (1) The free Ca2l concentration of the matrix of rat heart mitochondria ([Ca2`]m) was determined from the fluorescence of internalized indo-1. The value of the Kd of indo-I-Ca2" in the mitochondrial matrix was determined to be 95 nm, on the basis of equilibration of [Ca2"]m with the extramitochondrial free Ca2l ([Ca2"].) in the presence of rotenone, nigericin, valinomycin and Br-A23187. (2) [Ca2"]m responded to energization/de-energization protocols, the inhibition of Ca2"-uptake by Ruthenium Red and the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…Indeed, inhibition of pyruvate oxidation in the heart can readily occur independently of PDK phosphorylation of PDC. 40,41 We have also previously shown that glucose oxidation rates in the mouse heart can be dramatically altered independently of PDK phosphorylation and inhibition of PDC and that flux of pyruvate through PDC is regulated by fatty acid oxidation reaction products. 42 In the case of hearts from the mcd Ϫ/Ϫ mice, these fatty acid oxidation reaction products would be dramatically reduced after ischemia relative to wild-type hearts, likely relieving the inhibition of PDC.…”
Section: Dyck Et Al Reduced Ischemic Injury In MCD Ko Mouse Heartsmentioning
confidence: 94%
“…Indeed, inhibition of pyruvate oxidation in the heart can readily occur independently of PDK phosphorylation of PDC. 40,41 We have also previously shown that glucose oxidation rates in the mouse heart can be dramatically altered independently of PDK phosphorylation and inhibition of PDC and that flux of pyruvate through PDC is regulated by fatty acid oxidation reaction products. 42 In the case of hearts from the mcd Ϫ/Ϫ mice, these fatty acid oxidation reaction products would be dramatically reduced after ischemia relative to wild-type hearts, likely relieving the inhibition of PDC.…”
Section: Dyck Et Al Reduced Ischemic Injury In MCD Ko Mouse Heartsmentioning
confidence: 94%
“…• Ca 2þ Activation of OXPHOS: This hypothesis is based on the findings that not only the extramitochondrial ATPases, but also mitochondrial dehydrogenases, such as pyruvate dehydrogenase (PDH) (26), NADH-isocitrate dehydrogenase (ICDH) (27), and a-ketoglutarate dehydrogenase (a-KGDH) (28), can be activated by increased [Ca 2þ ] (Fig. 1).…”
Section: The Regulation Of Oxphosmentioning
confidence: 99%
“…؉ ratio in diploid and Ts16 neurons Increases in [Ca 2ϩ ] i may lead to intramitochondrial Ca 2ϩ accumulation, which in turn may increase respiration via activation of different intramitochondrial enzymes of the citrate cycle, namely pyruvate dehydrogenase, NAD ϩ -isocitrate dehydrogenase, and ␣-ketoglutarate dehydrogenase (Moreno-Sánchez and Hansford, 1988;Richter and Kass, 1991). Increased activity of the citrate cycle results in an increase in the NADH/NAD ϩ ratio (Duchen et al, 1993).…”
Section: Glutamate Induces Changes In Nad(p)h/nad(p)mentioning
confidence: 99%